Analisis Undang Undang yang Mengatur Jasa Konstruksi Indonesia Terhadap Pengguna dan Penyedia Jasa Konstruksi - Putra, Andi Bayu; Sulistio, Hendrik (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
Construction Services Law is a statutory regulation that is used to regulate all matters involving construction services, whereas in this study conducted in Jakarta, Indonesia, Law No. 18 of 1999 about Construction Services and Law No. 2 of 2017 about Construction Services. With changes in the Construction Services Law, there are differences in the form of revisions, additions, and reductions. These differences and changes are analyzed with the aim of developing a better Construction Services Law in the future. The method used in this research is a literature study method and questionnaire survey method. Questionnaire questions were formed based on literature studies from previous research and Construction Services Law discussed in this study. Data obtained from respondents were entered into the IBM SPSS Statistics 23 program and then conducted a validity test, reliability test, correlation test, and regression analysis. The analysis shows that there are several Construction Services Law’s regulations which cannot be a good guide for construction service providers and users yet, due to: the provisions regarding building failures are not well explained, the general lack of provisions governing the selection of expert assessors, the lack of clarity governing labor standards construction work and unclear regulations regarding sanctions for parties involved in construction work.